Market Power versus Efficient-Structure in Arab GCC Banking - Saeed Al-Muharrami; Kent Matthews (Cardiff University, Cardiff Business School, 2009)
This paper evaluates the performance of the Arab GCC banking industry in the context of the Structure-Conduct-Performance hypothesis in the period 1993-2002. The paper uses panel estimation differentiating between bank fixed effects and country fixed effects. It examines the Relative-Market-Power and the Efficient-Structure hypotheses differentiating between the two by employing a non-parametric measure of technical efficiency, and finds that the banking industry in the Arab GCC countries is best explained by the mainstream SCP hypothesis. The empirical results do not find any support for the Hicks (1935) Quiet Life version of the market power hypothesis.
Keywords: G2; L1; 330; GCC Banking; Structure Conduct Performance; Marktmacht; Struktur-Performance-Modell; Technische Effizienz; Islamische Bank; Arabische Golf-Staaten